Direct imaging of rotational stacking faults in few layer graphene. - Warner, J; Rümmeli, M; Gemming, T; Büchner, B; Briggs, G (2009)
Few layer graphene nanostructures are directly imaged using aberration corrected high-resolution transmission electron microscopy with an electron accelerating voltage of 80 kV. We observe rotational stacking faults in the HRTEM images of 2-6 layers of graphene sheets, giving rise to Moir patterns. By filtering in the frequency domain using a Fourier transform, we reconstruct the graphene lattice of each sheet and determine the packing structure and relative orientations of up to six separate sets. Direct evidence is obtained for few layer graphene sheets with packing that is different to the standard AB Bernal packing of bulk graphite. This has implications toward bilayer and few layer graphene electronic devices and the determination of their intrinsic structure.